Application of zirconium modified Cu-based oxygen carrier in chemical looping reforming. (June 2016) - Alirezaei, I.; Hafizi, A.; Rahimpour, M.R.; Raeissi, S.
Highlights: Different copper based Zr modified oxygen carriers are investigated in CO2 -CLR process. The presence of ZrO2 in the support structure inhibited the deposition of coke. The 15Cu/20Zr-Al oxygen carrier exhibited high stability and activity in CO2 -CLR. Complete methane conversion is achieved at relatively low temperature. Abstract: The modification of alumina support of copper-based oxygen carrier using zirconium oxide is investigated in this study. The CO2 modified chemical looping reforming (CO2 -CLR) process is applied to evaluate the synthesized oxygen carriers at different reduction temperatures (550–750 °C). The presence of ZrO2 in the support structure of oxygen carrier inhibited the deposition of coke on the samples. The results revealed that the addition of 20% zirconium oxide could effectively improve the efficiency of oxygen carrier at different reduction temperatures. In addition, the effect of CH4 /CO2 ratio in feed (0.5–3) and copper loading percentage (10, 15, 20, 25, 30) are investigated on methane and carbon dioxide conversion, hydrogen production yield and CO/CO2 ratio. The synthesized oxygen carriers were characterized by X-ray powder diffraction (XRD), field emission scanning electron microscopy (FESEM), BET and energy dispersive X-ray spectroscopy (EDX) techniques. The 15Cu/20Zr-Al as optimized oxygen carrier exposed a mesoporous structure with a high surface area of 315.9 m 2 g −1 . The redox results revealed that 15 Cu/20 Zr-Al oxygen carrier exhibited the highest activity and showed about 99.2% CH4 conversion at a low temperature of 650 °C. This oxygen carrier revealed high stability for CH4 and CO2 conversion, hydrogen production yield and CO/CO2 ratio during 16 redox cycles at 650 °C.